2023
DOI: 10.1002/pbc.30760
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of pre‐referral tumor resection in unilateral Wilms tumor: A single‐institute experience from a lower middle‐income country

Muhammad Saghir Khan,
Ata Ur Rehman Maaz,
Abid Quddus Qazi
et al.

Abstract: IntroductionThe objectives of this study were to evaluate the prognostic impact of pre‐referral surgical resection of Wilms tumor (WT) performed at non‐oncology centers, and to strategize an improved care plan for this very curable pediatric tumor.MethodsIn this study conducted in a large pediatric cancer center in Pakistan, we retrospectively reviewed the electronic medical records (EMR) of 149 patients with unilateral WT from September 2008 to August 2017. Based on treatment approach, patients were categoriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…pre-referral surgical resection of unilateral WT and concluded that the suboptimal pre-referral surgical intervention with no preoperative chemotherapy and delayed chemotherapy following the surgical resection led to poor survival outcomes in unilateral WT. 1 I would like to highlight some issues and propositions for this study while I applaud and congratulate the authors for their highly comprehensive and valuable study.…”
mentioning
confidence: 99%
“…pre-referral surgical resection of unilateral WT and concluded that the suboptimal pre-referral surgical intervention with no preoperative chemotherapy and delayed chemotherapy following the surgical resection led to poor survival outcomes in unilateral WT. 1 I would like to highlight some issues and propositions for this study while I applaud and congratulate the authors for their highly comprehensive and valuable study.…”
mentioning
confidence: 99%